The role of tourism in economic growth-outlook for the role of tourism in Iraqi marshes development. - عبد, احمد مزهر (Journal of Economics and Administrative Sciences, 2025)
The tourism activity is one of the pillars on which the economy of any country is based , the importance of the tourism sector is reflected in its potential to become an effective development alternative in many countries, especially Iraq ,this has a direct impact on the national economy as an important source in attracting hard currency and eliminating unemployment. Adding the Iraqi Marshlands to the list of effects makes it contribute to diversification of sources of income and stimulating rest of the economic sectors, the potentials and qualifications possessed by Iraq in the field of tourism and monuments have a significant impact on the state budget if they were exploited optimally. The research aims at identifying the contribution of the tourism sector to the advancement of the national economy because of its direct relationship with other sectors (productivity - commercial - service) , and its role in encouraging local and foreign investments , the research concluded that financial allocations should be made for the development of the Marshlands and the establishment of investment projects, and attracting the private sector in this field, in addition to supporting national products, especially the famous in the region, as well as encouraging craftsmen and setting up small factories and workshops that provide tourism market for this region.